PERKEMBANGAN PASAR TIKU DI KECAMATAN TANJUNG MUTIARA, KABUPATEN AGAM TAHUN 1980-2022 - Sari, Feni Afrina; Asri, Zul (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Abstract: This research examines the development of the Tiku Market in Nagari Tiku Selatan, Tanjung Mutiara District, Agam Regency (1980-2022). This research aims to examine the development of Tiku Market and to examine the existence of Tiku Market on the economic dynamics of Tiku Market traders. The method used in this research is the historical method with four stages: Heuristic historical research method, source criticism, interpretation, historiography. Tiku Market is a trading center market that can liven up the Tanjung Mutiara District area. The growth of this market began in 1942 by the people of three nagari spread across Tanjung Mutiara District, namely: Nagari Tiku Selatan, Nagari Tiku Utara and Nagari Tiku V Jorong. This market continued to develop, until the first construction took place from 1942 to 1980. Many developments were carried out during the New Order era, including Tiku Market. This market is one of the nagari's sources of income. In 1980, the development of Tiku Market began to be seen because this year renovation or construction of the market was carried out. The condition of the Tiku Market from 2010 to 2022 experienced a fairly stable condition, both in terms of sales turnover, the number of incoming merchandise, the levy system, the number of traders and buyers, and there were no problems with the organization and management of the market. The development carried out at Tiku Market is development carried out by several Tiku communities. The existence of the Tiku Market in Tanjung Mutiara District has had a very good influence on the emergence of various new jobs around the market.Keywords: Tiku Market, Development.